False Redemption—The Narrative Pattern of Korean Art Cinema - Bai, Song Xu (Frontiers in Communication, 2022)
Korean art cinema has an undeniable han favor, which is considered scholarly as the most characteristic aesthetic category of Korea. The iconic auteurs who pushed Korean brands to the international stages like Park Chan-wook, Kim Ki-duk and Lee Chang Dong, didn’t only gain their fame with their han films, but also prompted the dominated style, which is the han motif. This article extracted the common narrative pattern of the internationally acclaimed Korean art films by comparing and reading the films under the assumed pattern of false redemption. The parallel Christian redemption is a good supplement for the better understanding of false redemption. The false redemption is the most popular and effective pattern for expressing the han motif.